Classification of Bone Defects: An Extension of the Orthopaedic Trauma Association Open Fracture Classification. Issue 2 (February 2021) - Tetsworth, Kevin D.; Burnand, Henry G.; Hohmann, Erik; Glatt, Vaida
Abstract : Objectives: To develop a post-traumatic bone defect classification scheme and complete a preliminary assessment of its reliability. Design: Retrospective classification. Setting: Tertiary referral trauma center. Patients/Participants: Twenty open fractures with bone loss. Intervention: Assignment of a bone defect classification grade. Main Outcome Measurements: Open fractures were classified based on orthogonal radiographs, assessing the extent and local geometry of bone loss, including D1—incomplete defects, D2—minor/subcritical (complete) defects (<2 cm), and D3—segmental/critical-sized defects (≥2 cm). Incomplete defects (D1) include D1A—<25% cortical loss, D1B—25%–75% cortical loss, and D1C—>75% cortical loss. Minor/subcritical (complete) defects (<2 cm) (D2) include D2A—2 oblique ends allowing for possible overlap, D2B—one end oblique/one end transverse, and D2C—2 transverse ends. Segmental/critical-sized Defects (≥2 cm) include D3A—moderate defects, 2 to <4 cm; D3B—major defects, 4 to <8 cm; and D3C—massive defects, ≥8 cm. Reliability was assessed among 3 independent observers using Fleiss' kappa tests. Results: Interobserver reliability demonstrated the classification scheme has very good agreement, κ = 0.8371, P < 0.0005. Intraobserver reliability was excellent, κ = 1.000 (standard error 0.1478–0.1634), P < 0.00001. Interobserver reliability for the distinction between categories alone (D1, D2, or D3) was also excellent, κ = 1.000 (standard error 0.1421–0.1679), P < 0.00001. Conclusions: This classification scheme provides a robust guide to bone defect assessment that can potentially facilitate selection of the most appropriate treatment strategy to optimize clinical outcomes.